Octreotide in liver cirrhosis: a salvage for variceal bleeding can be a gunshot for kidneys - (:unkn) unknown (BLACKWELL PUBLISHING, 2005)
Background The renal effects of octreotide, used for bleeding esophageal varices in cirrhosis, are controversial. Methods: Fourteen, cirrhotic patients (Child-Pugh; A/B/C: 1/12/1) were enrolled. Plasma nitrite 3 and endothelin (ET) levels, urinary nitrite output, free water clearance (FWC) and fractional excretion of filtered sodium (FENa) were measured and renal Doppler ultrasound was carried out. Octreotide was infused at a rate of 0.75 mu g/kg/h for 3 h after a bolus of 0.75 mu g/kg body weight. All the parameters were reevaluated during octreotide administration while the patients acted as their own controls. Results: Octreotide induced significant reductions in urinary nitrite, FENa and FWC. Plasma ET levels increased (baseline: 6.7 pg/ml, octreotide: 8.4 pg/ml), whereas the plasma nitrite level did not change significantly after octreotide infusion. Overall, no significant change in renal resistive index (RRI) could be demonstrated on Doppler after octreotide administration. However, patients with elevated baseline RRI values had significantly more deterioration in FWC and FENa compared with patients with normal RRI in response to octreotide. Conclusion: A marked decrease in FENa, FWC and urinary nitrite output, together with a significant increase in plasma ET level in response to octreotide, may indicate renal dysfunction in cirrhotic patients. This deleterious renal effect of octreotide may be more enhanced in patients with elevated baseline RRI.
Keywords: cirrhosis; endothelin; octreotide; renal functions; renal pulsatility index; renal resistive index; POSTPRANDIAL SPLANCHNIC HYPEREMIA; PLASMA ENDOTHELIN LEVELS; RENAL-FUNCTION; HEPATORENAL-SYNDROME; PORTAL-HYPERTENSION; DOUBLE-BLIND; DOPPLER ULTRASONOGRAPHY; RESISTIVE INDEX; NITRIC-OXIDE; BLOOD-FLOW